Ultrasound driven bubbles in microfluidics. - Goh, Cui Ying. (2009)
Instead of using conventional valves, we look into using bubbles in microfluidics that are remotely-powered with an ultrasonic transducer to move and control fluid. The experimental approach was used in determining the ideal conditions for optimization of transduction. System adopted consisted of a glass slide with a soft polymer imprinted with microchannels plasma bonded to it. In the later section, bubbles in a flow-focusing device, coupled with ultrasound, were observed with an inverted microscope and high-speed camera.